PENGARUH STRUKTUR KEPEMILIKAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - -, YENI ARIYANTI (EKONOMIA, 2017)
Owner structure is the separation between the owner of company and manager of company. Laverage refers to the use of assets and find resources by company the company has to exclude the fixed expence.Hipothesis of the research is 1) owner structure and laverage influece significantly foward company value 2) owner structure influence significantly foward company value 3) Laverage influence significantly foward company valueThe anaysis instrument is multiple linier regresion the data used in the research is primary data. The linier equivalence from the regresion result of the research is Y = 0,446 – 0,845 + 0,004 + e.From the regresion equivalence it showa that X1 doesn’t influence significantly but X2 Influences significantly. It means there is no significant influence between owner structure and manufacture company value at Indonesia stack exchange. On the contrary, there is significant infuence between laverage and manuvacture company value. The research result shows that there is influence between owner structure and laverage with determinant coefisient value 0,313 or 31% influence 31% foward the manufacture company value stock excharge at indonesia.